Applicability of IT service management in the migration to cloud computing. - Cardoso, Abílio (2015)
The cloud computing (CC) paradigm is transforming the way Information Technology (IT) services are provided by converting IT products into services. This modification allows the delivery of IT services to end users in a way the customers stop purchasing products and start purchasing services instead. The successful migration to this paradigm by an organization requires a deep comprehension of its own IT as well as the dynamics of CC. To this purpose, a framework aggregating the activities that must be undertaken in two groups, the on premise and the off premise, was developed. The on premise group includes the actions developed by the customer, such as the development of a strategy plan, the attainment of a detailed definition of the organization processes and services and the definition of what to migrate to the cloud. The activities developed with the support of the candidates and selected CSPs are in the off premise group. This group encompasses activities such as the providers services’, the details ‘identification of the technologies related to the implementation of the organization processes into the cloud and the analysis of the conditions of service level agreement and the contract. Furthermore, there is already an extensive set of recommendations for IT management and IT governance in general – such as the Information Technology Infrastructure Library (ITIL) and the Control Objectives for Information and related Technology (COBIT) recommendations. However, the field of CC remains poorly covered. Acknowledging this state of affairs and adding the fact that CC is concerned with IT services, not to mention the number of organizations using ITIL in order to manage their IT services, the fact that ITIL is being recognized as a set of good practices, led to the decision of studying the applicability of service management, namely ITIL, to the migration of IT services to CC. The motivation of this study is related to the circumstance that organizations can take advantage of the work already carried out, the information gathered and the management of services when implementing ITIL. Additionally, if the customer and the supplier implement ITIL, the communication between them is also improved. Accordingly, a framework to migrate IT services, applications data and infrastructures to CC has been developed and the processes of this framework have been mapped to the ITIL’s framework.